New cell motility model observed in parasitic cnidarian Sphaerospora molnari (Myxozoa:Myxosporea) blood stages in fish - Hartigan, A; Estensoro, I; Vancová, M; Bílý, T; Patra, S; Eszterbauer, E; Holzer, A S (Scientific reports, 2016)
Cellular motility is essential for microscopic parasites, it is used to reach the host, migrate through tissues, or evade host immune reactions. Many cells employ an evolutionary conserved motor protein- actin, to crawl or glide along a substrate. We describe the peculiar movement of Sphaerospora molnari, a myxozoan parasite with proliferating blood stages in its host, common carp. Myxozoa are highly adapted parasitic cnidarians alternately infecting vertebrates and invertebrates. S. molnari blood stages (SMBS) have developed a unique "dancing" behaviour, using the external membrane as a motility effector to rotate and move the cell. SMBS movement is exceptionally fast compared to other myxozoans, non-directional and constant. The movement is based on two cytoplasmic actins that are highly divergent from those of other metazoans. We produced a specific polyclonal actin antibody for the staining and immunolabelling of S. molnari's microfilaments since we found that neither commercial antibodies nor phalloidin recognised the protein or microfilaments. We show the in situ localization of this actin in the parasite and discuss the importance of this motility for evasion from the cellular host immune response in vitro. This new type of motility holds key insights into the evolution of cellular motility and associated proteins.
Keywords: protilátky; Actins; fylogeneze; Cloning, Molecular; Phylogeny; klonování DNA; kapři; protozoální proteiny; Myxozoa; aktiny; Cell Movement; Antibodies; Animals; cytoplazma; Cytoplasm; zvířata; pohyb buněk; Carps; Protozoan Proteins